2006
DOI: 10.1111/j.2042-3306.2006.tb05564.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of proglycogen and macroglycogen in skeletal muscle of Standardbred trotters after intermittent exercise

Abstract: If the time between exercise sessions during training is too short the recovery period will be inadequate for complete restoration of muscle glycogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The horses performed a glycogen depleting field exercise test described by Bröjer et al [18]. In brief, the test included a 4000 m warm up at a slow trot, followed by 7 repeated 500 m up-hill intervals at a speed of 9 m/s and a down hill walk between each interval.…”
Section: Methodsmentioning
confidence: 99%
“…The horses performed a glycogen depleting field exercise test described by Bröjer et al [18]. In brief, the test included a 4000 m warm up at a slow trot, followed by 7 repeated 500 m up-hill intervals at a speed of 9 m/s and a down hill walk between each interval.…”
Section: Methodsmentioning
confidence: 99%
“…During prolonged submaximal intensity exercise, lipids also contribute to produce muscle energy with glycogen [ 10 ]. After exercise, supplementation of muscle glycogen can slowly take up to 72 h in horses [ 11 ]. Previous studies have shown that muscle glycogen supplement after exercise was enhanced by certain processes such as intravenous glucose infusion, oral acetate administration, and rehydration with hypotonic electrolyte solutions in horses [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, human studies have shown that protein is utilised to a greater extent when glycogen stores are lowered (Lemon and Mullin 1980;Blomstrand and Saltin 1999). This finding is of special interest concerning horses in race training, as Standardbred trotters generally are trained intensively 2-3 times per week and it can take up to 72 h for glycogen to be restored in muscle after intense exercise (Snow et al 1987;Hyyppä et al 1997;Bröjer et al 2006).…”
Section: Introductionmentioning
confidence: 99%